A novel alkaline phosphatase assay based on the specific chromogenic interaction between Fe3+ and ascorbic acid 2-phosphate. Issue 18 (30th April 2019) - Wang, Linjie; Ye, Kun; Pan, Jianming; Song, Hongwei; Niu, Xiangheng
Abstract : A new alkaline phosphatase sensing strategy based on the specific chromogenic interaction between ferric ion and ascorbic acid 2-phosphate was proposed. Abstract : In this work, a new colorimetric strategy based on the specific chromogenic interaction between Fe 3+ and ascorbic acid 2-phosphate was proposed for the highly selective, repeatable, and accurate detection of alkaline phosphatase with extremely simple operation and low cost.